Three-handed Saint in Erkech? (Research Announcements "Heritage BG", 2025)
This article deals with an image and inscriptions that appear on a bell from 1880 at the St Paraskeve church in Kozichino (former Erkech) village, Burgas region. The author offers a hypothesis for its origin, making connections with already known facts about the history of the said village. The most interesting here is the image of a saint with three hands, which is probably unique in the Christian Orthodox iconography. Offering parallels, vita reasons and iconographical logic here he suggests an identification ofthe holy personage. It must be St John of Damascus depicted with his cut right hand that holds a stick that symbolizes his melodist and hymnographic contribution to Christianity. Most probably the bell was produced in Kiev where the cult of the three-handed St Kazimir was known via Polish Catholicism and such a contamination was more possible then in the Balkans. References:Georgiev, Georgi. Erkechanite i tehniyat govor. – V: Izvestia na Seminara po slavyanski filologii pri Universiteta Sofia, kniga 2. Sofia, 1907, 133-200.Gergova, Ivanka. Chudesata na Presveta Bogoroditsa v kulturata na balgarskoto Vazrazhdane. Sofia, 2012.Kutsarov, Petar. Erkech. Burgas, 2001.Naydeonova, Goritsa. Godina – zhivot – istoria. Bitie i razpad na edna traditsionna kultura prez pogleda na etnomuzikologa. Sofia, 2023.Rëklaitis 1958: Rëklaitis, Polivas. Sv. Kazimiero koplyčia Vilniuje (II). Aidai 4 (April 1958). (109).
Keywords: Erkech village; Three-handed Virgin Mary; St John of Damascus; iconography